A criação de uma animação 3D - Detoni, Aramis de Oliveira (2012)
This paper presents a practical experience of the cration of a 3D animation. It was present here the steps involved in relation to the work of a graphic designer in a film production. Stated some of design concepts that can be applied within that area. This work was developed since the creation of the script until the compilation of formats for viewing, through the creation of scenarios, characters, storyboard, etc. It was excluded any activities of graphic designers for the dissemination of a film. All work presented focuses only in creating the cinematic.